Analisis Kesiapan Guru dalam Mengimplementasikan Pendidikan Multikultural pada Pembelajaran Abad Ke-21 : Penelitian - Mia Sumiarsih; Siti Fadjarajani; Gumilar Mulya; Iis Marwan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Multicultural education in 21st-century learning requires teachers who are pedagogically skilled, culturally sensitive, emotionally adaptive, and digitally literate. This study explores teachers’ readiness to implement multicultural values through a qualitative case study in a culturally diverse vocational school. Data were obtained from semi-structured interviews, classroom observations, and document analysis. The findings show that teachers generally understand the importance of multicultural principles; however, variations remain in pedagogical design, intercultural interaction skills, conflict management, and digital media utilization. Limited professional development, minimal integration of local cultural resources, and resistance to change are recognized as current barriers. Strengthening institutional support and continuous teacher training is essential to empower teachers as cultural mediators who foster inclusive learning environments. This study highlights the urgency of enhancing teacher readiness so multicultural education can be applied more effectively in classroom practice.